Performance of Polycarbonate Concrete Panels in Construction: A Critical Research Review - Ab Rahim, Nur Rahmat; Dr Seyed Jamalaldin Seyed Hakim, (Recent Trends in Civil Engineering and Built Environment, 2022)
A unique category in polymer heat and thermal conductivity conjures a huge leap in sustainable construction by emphasizing the thermal insulation system. Combining polycarbonate with concrete panels to create a new manufacturing method called concrete panels. Polycarbonate concrete panels may offer excellence and thermal comfort insulator. In a building, energy efficiency is the most essential element in converting a building system to a green building plan. This study includes the evaluation of Precast Concrete Sandwich Panels (PCSP), the junction of the concrete panel to bind to a wall or a roof with polycarbonate panels, and easy temperature insulation in concrete panels. By following the Green Building Index (GBI) rate, issues that may be faced include harmful gas emissions such as CO2 resulting in an impact on atmospheric temperature or termed greenhouse phenomena. By reviewing such critical research on sustainable building or technologies, many articles will be discussed such as compliances of foam concrete as wall panels, isolation mechanism in concrete panels, heat transfer properties in the vacuum insulation wall, and CO2 emission effect to the environment. A comprehensive evaluation of current literature on thermal, optical and acoustic performance of polycarbonate concrete panels for sustainable built environment is explored in this study.